Introduction -- Broadening Teacher Candidates' Horizons: An Introduction to the Teacher Education Reciprocal Learning Program - Shijing Xu (University of Windsor, 2019)
The Teacher Education Reciprocal Learning Program (RLP) is a collaborative initiative between the University of Windsor (UW), Canada, Southwest University (SWU), China, in partnership with Greater Essex County District School Board and Chinese schools associated with SWU.  The program, founded in 2010 through SWU Teacher Education fund and UW Strategic Priority Fund with in-kind contributions from Greater Essex County District School Board, is designed to provide an exceptional experience with international engagement, to broaden teacher candidates' horizons for a society of increasing diversity, to foster international collaboration among faculty members who are interested in cross-cultural studies and multicultural education, and to enhance the international reputation of the University of Windsor (Xu, 2011a). The RLP is one of the foundational programs which provide research contexts and settings for the Social Sciences and Humanities Research Council (SSHRC) Partnership Grant Project entitled "Reciprocal Learning in Teacher Education and School Education between Canada and China" (Xu & Connelly, 2013-2020).